Keterwakilan Perempuan dalam Ranah Politik & Urgensi Keterwakilannya: Tinjauan Pengambilan Keputusanya Prespektif Bimbingan Konseling - Mu'awanah, Elfi (Ta'allum: Jurnal Pendidikan Islam, 2013)
Becoming woman representatives either in politics or other organizations requires good will, self- support, and morality. If necessary, it requires supernatural and spiritual strength. The biggest challenge of woman representatives is how they can maintain their family’s harmony and unity. This must always be the main target of success of any woman representatives.